Ubiquitous Transgenic Overexpression of C-C Chemokine Ligand 2: A Model to Assess the Combined Effect of High Energy Intake and Continuous Low-Grade Inflammation - Rodríguez-Gallego, Esther; Riera-Borrull, Marta; Hernández-Aguilera, Anna; Mariné-Casadó, Roger; Rull, Anna; Beltrán-Debón, Raúl; Luciano-Mateo, Fedra; Menendez, Javier A.; Vazquez-Martin, Alejandro; Sirvent, Juan J.; Martín-Paredero, Vicente; Corbí, Angel L.; et al. (Mediators of Inflammation, 2013)
Excessive energy management leads to low-grade, chronic inflammation, which is a significant factor predicting noncommunicable diseases. In turn, inflammation, oxidation, and metabolism are associated with the course of these diseases; mitochondrial dysfunction seems to be at the crossroads of mutual relationships. The migration of immune cells during inflammation is governed by the interaction between chemokines and chemokine receptors. Chemokines, especially C-C-chemokine ligand 2 (CCL2), have a variety of additional functions that are involved in the maintenance of normal metabolism. It is our hypothesis that a ubiquitous and continuous secretion of CCL2 may represent an animal model of low-grade chronic inflammation that, in the presence of an energy surplus, could help to ascertain the afore-mentioned relationships and/or to search for specific therapeutic approaches. Here, we present preliminary data on a mouse model created by using targeted gene knock-in technology to integrate an additional copy of the CCl2 gene in the Gt(ROSA)26Sor locus of the mouse genome via homologous recombination in embryonic stem cells. Short-term dietary manipulations were assessed and the findings include metabolic disturbances, premature death, and the manipulation of macrophage plasticity and autophagy. These results raise a number of mechanistic questions for future study.